A new species of Notiphilides from Amazonia, with a redescription of N. grandis (Chilopoda, Geophilomorpha, Oryidae) - Calvanese, Victor C.; Brescovit, Antonio D. (Zootaxa, 2017)
Notiphilides grandis Brölemann, 1905 is here redescribed based on the female holotype and specimens recently collected in the type locality, Manaus, state of Amazonas, Brazil, and the male is described for the first time. Notiphilides amazonica sp. n. is described based only on female specimens from Peru and Brazil. We provide a key and distribution map for the known species of Notiphilides.